Macadamia Oil Supplementation Attenuates Inflammation and Adipocyte Hypertrophy in Obese Mice - Lima, Edson A.; Silveira, Loreana S. [UNESP]; Masi, Laureane N.; Crisma, Amanda R.; Davanso, Mariana R.; Souza, Gabriel I. G.; Santamarina, Aline B.; Moreira, Renata G.; Martins, Amanda Roque; Sousa, Luis Gustavo O. de; Hirabara, Sandro M.; Rosa Neto, Jose C. (Hindawi Publishing Corporation, 2014)
Excess of saturated fatty acids in the diet has been associated with obesity, leading to systemic disruption of insulin signaling, glucose intolerance, and inflammation. Macadamia oil administration has been shown to improve lipid profile in humans. We evaluated the effect of macadamia oil supplementation on insulin sensitivity, inflammation, lipid profile, and adipocyte size in high-fat diet (HF) induced obesity in mice. C57BL/6 male mice (8 weeks) were divided into four groups: (a) control diet (CD), (b) HF, (c) CD supplemented with macadamia oil by gavage at 2g/Kg of body weight, three times per week, for 12 weeks (CD + MO), and (d) HF diet supplemented with macadamia oil (HF + MO). CD and HF mice were supplemented with water. HF mice showed hypercholesterolemia and decreased insulin sensitivity as also previously shown. HF induced inflammation in adipose tissue and peritoneal macrophages, as well as adipocyte hypertrophy. Macadamia oil supplementation attenuated hypertrophy of adipocytes and inflammation in the adipose tissue and macrophages.